Measure of Stage Migration Due to Significant Nodes Detected on Imaging in Patients with Uterocervical Cancer Using the FIGO 2018 Staging System - Nappoly, Renata; Chandramohan, Anuradha; Thomas, Vinotha; Daniel, Sherin (Journal of Gastrointestinal and Abdominal Radiology, 2025)
While the earlier International Federation of Gynecology and Obstetrics (FIGO) staging guidelines for carcinoma cervix were only based on clinical examination findings, the revised guidelines published in 2018 incorporated imaging and pathological assessments to the staging system.This article compares the imaging-based new FIGO staging system with the old clinical staging and assesses the degree of stage migration.In this institutional review board-approved retrospective study, consecutive patients who were diagnosed with uterocervical cancer and underwent imaging (i.e., computed tomography [CT]/magnetic resonance imaging [MRI]/positron emission tomography-CT [PET-CT]/ultrasound [USG]) between 2013 and 2017 were reviewed. Imaging findings were documented, and stage was assigned as per the revised 2018 FIGO staging system for cervical cancer and compared with the previous FIGO staging system. The degree of stage migration was compared between the new and the old FIGO staging systems. The degree of stage migration due to significant lymph nodes detected on different imaging modalities was assessed.274 patients with a mean age of 51 years and a range of 20 to 80 years were reviewed. The distribution as per the FIGO 2009 were: 0.3% (n = 1) in stage IA1 and IA2, 6.2% (n = 17) in stage IB1, 1% (n = 3) in stage IB2, 4% (n = 11) in stage IIA, 44.5% (n = 122) in stage IIB, 0.7% (n = 2) in stage IIIA, 27% (n = 74) in stage IIIB, 5.8% (n = 16) in stage IVA, and 7.2% (n = 20) in stage IVB. Among all these patients, 66.4% (n = 182) patients underwent USG, 53.6% (n = 147) underwent CT, 42.7% (n = 117) had MRI, and 3.6% (n = 10) underwent PET-CT. Only 4% (n = 8) and 0.5% (n = 1) patients who underwent USG at staging were detected to have significant parailiac and para-aortic nodes, respectively. On the other hand, 7.66% (n = 21) had significant para-aortic and 44.16% (n = 121) had significant parailiac nodes on other cross-sectional imaging modalities. There was stage migration in 36.86% of patients, with 23.72% upstaged to stage IIIC1.Fewer lymph nodes were detected on USG than other cross-sectional imaging modalities. Adopting the new FIGO resulted in stage migration in 36.86% of patients, predominantly due to lymph node metastases detected on imaging.
Keywords: uterocervical cancer; carcinoma cervix; stage migration; FIGO 2018; lymph node metastasis